Systemic Lupus Erythematosus Presenting with Massive Ascites: A Case of Pseudo-Pseudo Meigs Syndrome - S. McVorran; J. Song; V. Pochineni; A. Abrudescu-Opran (Case Reports in Rheumatology)
The case presented is consistent with the phenomenon known as Pseudo-Pseudo Meigs Syndrome (PPMS). In it, we describe a young woman with newly diagnosed Systemic Lupus Erythematosus presenting with ascites, pleural effusions, and an elevated CA-125 level. Although rare, and of uncertain etiology, PPMS is becoming increasingly recognized in the literature. It should be considered as a differential diagnosis in such patients, along with the search for malignancy.